Social trends in singleton births and birth weight in Wirral residents, 1990–2001. Issue 5 (1st September 2003) - Bundred, P; Manning, D; Brewster, B; Buchan, I
Abstract : Objective: To examine social trends in the number of singleton births and birth weight in an English health district between 1990 and 2001, using an area based deprivation index. Design: Analysis of routinely collected hospital data. Setting: Wirral Health District in north west England. Participants: All 48 452 live births to Wirral residents from 1990 to 2001. Main outcome measures: Birth numbers, birth weight, and standard deviation score for birth weights for singleton births. Townsend material deprivation scores derived from postcodes. Results: The number of singleton births fell by 28% over the 12 years. The fall in the least deprived Townsend quartile (45%) was more than triple that in the most deprived quartile (γ = 0.045; 95% confidence interval (CI) = 0.036 to 0.054; p < 0.001). Over the study period, the mean birth weight in the least deprived Townsend quartile was 141 g higher than in the most deprived quartile. There was a highly significant association between the standard deviation score for birth weight and Townsend quartile (τ-b = −0.062; 95% CI = −0.068 to −0.055; p < 0.001). Numbers of low birth weight babies in the least deprived quartile fell disproportionately compared with those from the most deprived quartile (γ = 0.17; 95% CI = 0.09 to 0.25; p < 0.001). Conclusion: The reduction in birth rate in the Wirral was significantly less in the most deprived districts. This was accompanied by related differences in mean birth weight and the number of low birth weight babies, indicating increasing social inequality in birth trends. Previously described social inequity in birth weight and the number of low birth weight babies continues in the north west of England.